INCREASING CAROTEN IN SWEET BREAD WITH PUREE SUBSTITUTION OF ORANYE ORDER PALM IN WHEAT FLOUR - Ichda Chayati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2011)
The objectives of this study were to investigate : 1) the process for making orange-fleshed sweet potato puree, 2) substitution of orange-fleshed sweet potato puree to wheat flour in bread making, 3) evaluation of consumer preference to bread of orange-fleshed sweet potato puree (roti manis puree ubi jalar oranye-RMP), 4) total carotene changes during RMP making, 5) total carotene and texture differences between bread (roti manis standar-RMS) and RMP, and 6) economic liability of RMP. Hedonic test was carried out by preference test using 80 panelists. Moisture content was analyzed using gravimetric method, texture was analyzed using Lloyd, and total carotene content was analyzed using spectrophotometer method. Research design was completely randomized design, duplicate samples and triplicate analysis. One way anova was carried out to analyze data of total carotene and followed by LSD test, while t-test was carried out to determine significant differences of total carotene and texture between RMS and RMP. P values 0.05 were considered statistically significant. Economic liability was determined using price and BEP. Results showed that: 1) processing steps for making puree were cleaning, steaming, peeling, and mashing, 2) maximal incorporation of puree for making RMP was 60%, 3) consumer preference to RMP 60% was the same as to RMP 40 and 50%, 4) total 13 110 carotene decreased 37,9% during RMP making, 5) total carotene of RMP was higher than RMS, while the texture was softer, and 6) RMP was economically liable.